2018
DOI: 10.1016/j.nepr.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Assessing levels of student nurse learning in community based health placement with vulnerable families: Knowledge development for future clinical practice

Abstract: It is essential that universities collaborate with industry and consumers to ensure that the undergraduate programs offer a high standard of care and address current trends in the health care industry. There is a growing need for workforce development in primary healthcare and an increased understanding about how adversity can lead to ill health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The results of the present systematic review suggest the use of community-based teaching enhances the confidence of undergraduate nursing students. Researchers found that engaging nursing students in the community and confronting their problems increased students' confidence in caring for people in the community [11,20,21,23,24,[26][27][28]32]. The findings of the present study are consistent with the findings of other studies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of the present systematic review suggest the use of community-based teaching enhances the confidence of undergraduate nursing students. Researchers found that engaging nursing students in the community and confronting their problems increased students' confidence in caring for people in the community [11,20,21,23,24,[26][27][28]32]. The findings of the present study are consistent with the findings of other studies.…”
Section: Discussionsupporting
confidence: 89%
“…1. Seventeen articles published during 2004-2020 were included: including five quasi-experimental studies, three descriptive studies, four mixed method studies, and five qualitative studies [11,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The total number of participants was 1,866, ranging from 14 to 613 in each study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students in health‐related professions need exposure to vulnerable populations to disperse any stereotypes they may hold 12 . Exposure to different cultures and socioeconomic situations enlighten health‐related students with the knowledge, understanding, and sensitivity to strengthen relationships with vulnerable populations, such as those experiencing homelessness 16 …”
Section: Call To Actionmentioning
confidence: 99%
“…Hence, knowledge about the number of children exposed to this type of disadvantage has only recently begun to reflect the actual depths of the issue. The additional advantage of this initiative is that specialist homeless services are often the first to know when children are at risk of abuse, neglect or disconnection from other services, suggesting that closer integration with authorities may help them to intervene faster (Flatau et al, 2018; Hudson et al, 2014; Parry & Abbott, 2017; Parry & Abbott, 2018; Parry et al, 2009; Parry et al, 2018; Parry & Willis, 2013; Pennsylvania Chapter of the American Academy of Pediatrics, 2014). However, until such service link ups are more integrated, interventions tied to specialist homeless services (such as the Nurse Practitioner model of care) cannot provide immediate health interventions (AAP, 2013; AIFS, 2012; AIHW, 2012, 2017; Bedford et al, 2013; Davidson et al, 2018; Duncan et al, 2010; Goldfeld et al, 2017; Hurley et al, 2018; Parry, Grant, & Burke, 2016; Pungello et al, 2010; Sandstrom & Heurta, 2013; Smith Family, 2019).…”
Section: Introductionmentioning
confidence: 99%